Development of moral judgment in married and divorced people of the city of Arequipa - Murillo Deglane, María Gracia (2015)
A Descriptive-comparative study. 70 people from which 35 were married and 35 were divorced were evaluated with Lind test both individually and collectively and virtual way. Significant differences between groups (Sig. Bilateral 0,000 in the test of equal means for the index C and Moral Attitude) were found. Married people are more capable of moral judgment, lower levels of moral attitude and are in higher stages of moral judgment development; thus clearly demonstrating that the married group has a better development of moral judgment than the group of divorced people.